Analisis SWOT dalam Meningkatkan Konsep Kreatif Pelaksanaan Event Tahunan Fin Expo - Cecilia, Anastasia; Wirata, I Nengah; Kusumarini, Indah (Journal of Tourism and Hospitality Analysis (JoTHA), 2024)
The study entitled " SWOT Analysis in Enhancing the Creative Concept of the Annual Fin Expo Event" aims to understand the SWOT of the creative concepts of Fin Expo 2023, based on the four dimensions of creativity, namely Persons, Processes, Products, and Press. The data was collected through with OJK as client and CV. Kopi Panas as the event organizer. The technique used is descriptive analysis to measure the level of satisfaction of visitors with the creative dimensions and SWOT analysis. Based on SWOT analysis, several strategies were found to be applicable, namely: (1) the SO strategy utilizes creative team expertise in collaborating various activities such as talkshows, contests, and unique cultural parades to attract more visitors, (2) the ST strategy relies on the strength of the variable event concept to address threats from other more experienced event organizers, (3) the WO strategy includes improved internal communication between the creative team and the field design team to optimize the setting of the event and develop educational content, and (4) the WT strategy improves the event content and the use of technology to improve visitors' accessibility.